Understanding emoji attributes in instant messaging apps / Azahar Harun, Mohamed Razeef Abd Razak and Mohd Zaki Mohd Fadil - Harun, Azahar; Abd Razak, Mohamed Razeef; Mohd Fadil, Mohd Zaki (Unit Penerbitan, UiTM Kelantan, 2021)
Emoji are pictographs that represent emotion, opinions, ideas, feelings, and reactions concerning a matter or an event. Unlike the traditional text-based system, Emoji possesses anthropomorphic attributes which are widely used in Instant Messaging (IM) apps. In spite of this, the fundamental questions of how the anthropomorphic attributes of Emoji can influence emotion and why users prefer them as a medium of communication are rarely discussed in the design context. Therefore, the objective of this study is twofold: first, to analyze Emoji characters, and secondly, to evaluate the user's response. Eight categories of Emoji characters, Happy, Angry, Sad, Unwell, Love, Fear, Shy and Funny, were selected as samples. The findings show that the anthropomorphism perception of the users towards the selected samples is unique and distinctive. In regard to the user’s response, the results show a higher combined mean in terms of Perceived Anthropomorphism and Perceived Usefulness. The study concluded that basic anthropomorphic attributes and graphic elements of Emoji characters crucially play a significant role in representing the intended expression. Having said that its practicality rests on the aspect of familiarity and usefulness. It is hoped that this study would help enhance knowledge regarding the anthropomorphic attributes and the development of future Emoji characters in IM apps